Study of formation of dorsal venous arch of the hand in both sexes - P., Ramesh; Kumar T., Dhinesh; C., Deepa; T., Kalyani; D., Anupama (International Journal of Research in Medical Sciences, 2024)
Background: The dorsal venous arch (DVA) is a superficial venous network of the hand. It is formed by the union of four dorsal metacarpal veins in the middle of the dorsum of the hand. Medially and laterally the dorsal venous arch continues as basilic and cephalic veins respectively. Commonly, these veins are chosen for intravenous procedures, the most prominent being the dorsal metacarpal veins. The present study aims to study the different types of formation of dorsal venous arch in both the sexes. Methods: 100 hands of voluntary participants were studied (50 male hands, 50 female hands) in St Peter’s Medical College, Hospital and Research Institute, Hosur, Tamil Nadu. The rubber tourniquet was tied 1 hand breadth above the wrist to make the veins prominent and observed the pattern of formation of DVA with laterality and sex being noted. Results: In the present study, the formation of dorsal venous arch, commonly type 2 pattern in males and type 1 pattern in females were observed. The prominent venous pattern was observed in males and on the lateral side of the dorsal metacarpal veins. Conclusions: The present study carried out to enlighten the vascular surgeons, postgraduates, interns, paramedics and nurses regarding the knowledge of different types of the formation of dorsal venous arch of hand, so that hassle free procedures can be carried out on these superficial veins of hands at the time of routine and emergency situations.